2014
DOI: 10.5993/ajhb.38.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Financial Strain and Self-rated Health among Black Adults

Abstract: Objectives To explore associations between financial strain and self-rated health among 1341 Black adults. Methods Associations were investigated using a covariate-adjusted linear regression model. Mediation (via stress and/or depressive symptoms) was explored in additional models using a nonparametric bootstrapping procedure. Results Higher financial strain was associated with poorer self-rated health (p < .001). Stress and depressive symptoms were each significant mediators of this relation in both singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 42 publications
5
21
0
Order By: Relevance
“…12,[45][46][47] Further research is needed to better understand how hardship conditions affect HIV risk for Black MSM, including exploring intersections between measures of various types and levels of hardships. Future research can build on these results by exploring whether individual-level hardships interact with area-level hardships to predict HIV risk in Black MSM and what is the impact of geo-political location on these associations.…”
Section: Discussionmentioning
confidence: 99%
“…12,[45][46][47] Further research is needed to better understand how hardship conditions affect HIV risk for Black MSM, including exploring intersections between measures of various types and levels of hardships. Future research can build on these results by exploring whether individual-level hardships interact with area-level hardships to predict HIV risk in Black MSM and what is the impact of geo-political location on these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive work has implicated a robust association between financial stressors and poorer self-rated health. 14,19,42 As such, the benefit of general social support may not be strong enough to combat this association. Importantly, however, other research suggests that perceived social support related to specific groups (eg, church-based social support) may be more pertinent to the relation between financial strain and self-rated health than perceived social support more generally (ie, not organization specific).…”
Section: Discussionmentioning
confidence: 99%
“…17 Indeed, initial empirical evidence suggests that greater financial strain contributes to poor self-rated health (1 element of HRQoL) after controlling for objective SES. 18,19 Thus, despite overlap between subjective and objective financial strain, 20 the uniqueness of subjective financial strain appears to affect HRQoL to a greater extent. However, this line of research has been limited to only one aspect of HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, black adults are more likely to report fi nancial strain (Savoy et al, 2014 ;Shippee, Wilkinson, & Ferraro, 2012 ;Szanton, Thorpe, & Whitfi eld, 2010 ). In another study, black males, black females, and white females were shown to be less satisfi ed fi nancially after also accounting for perceived income adequacy (DePianto, 2011 ).…”
Section: Financial Satisfactionmentioning
confidence: 99%
“…Connections between life course fi nancial strain and health have been made for African American adults and even black women who are known to disproportionately head households with minor dependents (Savoy et al, 2014 ;Shippee et al, 2012 ). Also, among 10 research priorities identifi ed in 2008 by 29 scholars at the National Research Symposium on Financial Literacy and Education in Washington D.C., two of the priorities called for a better understanding of racial and ethnic disparities in consumer fi nance issues such as fi nancial socialization (Schuchardt et al, 2009 ).…”
Section: Conclusion and Future Research Suggestionsmentioning
confidence: 99%